Isolated Congenital Bilateral Choanal Atresia and Nasopharyngeal Atresia- a case report - Das, Suman; Sarkar, Nirmalya; Chatterjee, Kaushani; Paul, Ayan (Bangladesh Journal of Medical Science, 2013)
A term neonate developed respiratory distress, paradoxical cyanosis (relieved by crying) soon after birth. Inability to insert No.5 French infant feeding tube through the nose into the pharynx led to the diagnosis of Bilateral Choanal Atresia , which was confirmed by HRCT Scan of the nose. Insertion of an oropharyngeal tube reduced the respiratory distress. Extensive investigations did not reveal any other congenital anomaly. The baby was treated with Transnasal Surgery. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14454 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 91-94